2011
DOI: 10.4054/demres.2011.25.8
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in social mortality differentials in Switzerland (1990-2005)

Abstract: Using data from the 1990 and 2000 Swiss Federal Censuses linked to the death records of the years 1990-1995 and 2000-2005, this paper investigates gender differences in mortality differentials by level of educational achievement and by marital status. In both periods, the differential by level of education is clearly more pronounced among men, but the difference in the educational gradient between men and women decreases between the two periods of observation. Health behavior might contribute to the gender dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 19 publications
0
6
0
4
Order By: Relevance
“…However, a tactic for surmounting this difficulty is to link administrative data containing vital events with survey or census data containing demographic and socio-economic information. Extant immigrant mortality studies using linked data are mostly from Europe (Kyobutungi et al 2006;Blomgren and Valkonen 2007;Bos et al 2007;Ott et al 2008;Martikainen et al 2009;Schumacher and Vilpert 2011;Zarulli et al 2012), the USA (Abraído-Lanza et al 1999;Singh and Siahpush 2002;Palloni and Arias 2004;Arias et al 2010;Borrell and Lancet Owing to data limitations, previous studies on immigrant mortality in Canada could not concurrently test for place of birth and period of immigration, or account for relevant factors such as socio-economic status in order to get a true picture of the effect of immigration on mortality (Trovato 2003;DesMeules et al 2004DesMeules et al , 2005. However, recent developments in data organization, involving the linking of survey and census data to administrative data in Canada, have transformed the situation and have opened up the potential for empirical testing of diverse hypotheses on health including those related to immigration (Hwang et al 2009;Wilkins et al 2009;Sanmartin et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…However, a tactic for surmounting this difficulty is to link administrative data containing vital events with survey or census data containing demographic and socio-economic information. Extant immigrant mortality studies using linked data are mostly from Europe (Kyobutungi et al 2006;Blomgren and Valkonen 2007;Bos et al 2007;Ott et al 2008;Martikainen et al 2009;Schumacher and Vilpert 2011;Zarulli et al 2012), the USA (Abraído-Lanza et al 1999;Singh and Siahpush 2002;Palloni and Arias 2004;Arias et al 2010;Borrell and Lancet Owing to data limitations, previous studies on immigrant mortality in Canada could not concurrently test for place of birth and period of immigration, or account for relevant factors such as socio-economic status in order to get a true picture of the effect of immigration on mortality (Trovato 2003;DesMeules et al 2004DesMeules et al , 2005. However, recent developments in data organization, involving the linking of survey and census data to administrative data in Canada, have transformed the situation and have opened up the potential for empirical testing of diverse hypotheses on health including those related to immigration (Hwang et al 2009;Wilkins et al 2009;Sanmartin et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Life expectancy at age 65 for the high education group in Finland, Sweden, Norway and Switzerland. Data sources for the high education group: (a) unpublished data by Statistics Finland, Statistics Norway, and Statistics Sweden, (b) Martikainen et al [54] for Finland (2001-2010), and (c) Schumacher and Vilpert [53] for Switzerland. Life expectancy at age 65 for the British Royal Society members.…”
Section: Longevity Advances and Educationmentioning
confidence: 99%
“…Previous research, for example, Schumacher and Vilpert (2011), has shown that social inequalities in mortality are structured by gender. This paper has also highlighted the fact that factors shaping mortality differ by sex.…”
Section: Discussionmentioning
confidence: 98%